Mobile Technologies and Applications for the Internet of Things Proceedings of the 12th IMCL Conference - Auer, Michael E.; Tsiatsos, Thrasyvoulos (Advances in Intelligent Systems and Computing, 2019)
XVI, 406 p. 181 illus., 161 illus. in color.